The opacity of the extragalactic medium to gamma radiation - Pimentel, Douglas Roberto de Matos (2019)
In this thesis a detailed study of the interaction between gamma-rays coming from active galactic nuclei (AGN) and the radiation field generated by the thermal emission from all the galaxies, the extragalactic background light (EBL), is performed. The development of the imaging air Cherenkov telescope (IACT) technique has been providing well determined spectral energy distributions (SED) of extragalactic sources and, in turn, allowing investigations of the attenuation processes of very high energy (VHE) radiation by the EBL. In 1997, a flare state of the blazar Markarian 501 (Mkn 501) provided flux measurements at energies up to ~ 20 TeV. We show that this spectrum is the one with the highest expected attenuation by the EBL dust component among the current known TeV emitters. Starting from an EBL model based on stellar and dust blackbody contributions, we were able to investigate the role of each EBL component in the attenuation of Mkn 501 SED. In such EBL model, dust is divided into three different grain types (polycyclic aromatic hydrocabons (PAH), small (SG) and large grains (LG)) and the importance of each one of these components to the opacity of the extragalactic medium for the Mkn 501 SED could be better understood. In particular, PAH molecules have a fundamental importance in the description of Mkn 501 spectrum, because its slope observed around 10 TeV can only be correctly described by this dust component. On the other hand, an effective model containing only PAH as dust can be excluded with a significance of at least 5 $\\sigma$, independently of the intrinsic spectrum assumed. Finally, a forecasting study is performed for the third generation of IACT, the Cherenkov Telescope Array (CTA). Through a maximum likelihood estimator we show that, already for a single source analysis, the PAH relative contribution can be determined with a good resolution for 50 hours of observation. The combination of several observations shows that 30 minutes of exposure time is enough to determine the PAH fraction with a reasonable resolution. The impact of the redshift uncertainties is also analyzed considering an a priori probability for this observable when determining the PAH fraction.